Komparasi Tentang Masa Iddah Antara Kompilasi Hukum Islam dan Kitab Undang-Undang Hukum Perdata - DERMINA DALIMUNTHE (El-Ahli : Jurnal Hukum Keluarga Islam, 2023)
The waiting period after the breakup of a good marriage caused by death, divorce, and court decisions is an act regulated in the Compilation of Islamic Law and the Civil Code which has differences and similarities in concept, with the aim of knowing thoroughly about the waiting period, the difference findings are the length of the waiting period 90 days in KHI, and 300 days in the Civil Code. The provisions for the iddah period in KHI are very clear and detailed and in the Civil Code it is very limited. The similarity of the iddah period in Islamic law and the Civil Code is that it prohibits new marriages before the end of the iddah or waiting period, and the iddah period is calculated from the fall of a court decision that has permanent legal force. The purpose of the iddah period in Islamic law and the Civil Code is to prevent mixing of seeds or confistus sanginis (hereditary doubts).